New Technologies in Cereal Processing and Their Impact on the Physical Properties of Cereal Foods - Min Li; Meng Niu (Foods, 2023)
Cereal is a general term for cereal plants or food crops, covering a wide range of foods, including rice, wheat, millet, corn and other miscellaneous grains, and representiing the most important component of the human diet [...]